Enhancing germination performance and vigor of lettuce and napa cabbage seeds through simple seed priming techniques under controlled conditions - ROFIQOH PURNAMA RIA; FITRA FADHILAH RIZAR; DEDIK BUDAINTA; MARLIN SEFRILA; FITRA GUSTIAR (Smujo International, 2026)
Abstract. Ria RP, Rizar FF, Budainta D, Sefrila M, Gustiar F. 2026. Enhancing germination performance and vigor of lettuce and napa cabbage seeds through simple seed priming techniques under controlled conditions. Asian J Agric 10: g100175. https://doi.org/10.13057/asianjagric/g100175. Introduced leafy vegetable seeds marketed for urban farming are often subjected to prolonged storage and suboptimal handling before use, which may reduce seed vigor, delay germination, and lead to non-uniform seedling emergence. This study evaluated simple seed priming treatments to improve germination performance in four commercial leafy vegetable seed types: butterhead lettuce, red romaine lettuce, green lettuce, and napa cabbage. The experiment was conducted in September 2025 at the Seed Technology Laboratory, Universitas Sriwijaya, Indonesia, using a factorial completely randomized design. Seeds were subjected to four treatments: untreated control, warm water priming at 60°C for 15 minutes, 60% shallot extract for 30 minutes, and 70% coconut water for 30 minutes. Germination percentage was recorded every 6 hours (h) for 48 h, and physiological parameters, including T50, Mean Germination Time, Germination Index, Vigor Index, Relative Germination Index (RGI), and shoot emergence percentage, were calculated. Warm water reduced T50 to 18.48 h and shallot extract to 19.38 h, compared with 36.69 h in the control, indicating faster germination. These findings indicate that warm water and shallot extract are promising simple priming methods for improving the laboratory germination performance of commercial leafy vegetable seeds, although validation under nursery or field conditions is still needed.